Three-dimensional quantification of pore structure in coal ash-based geopolymer using conventional electron tomography - Lee, S.; Jou, H.; Van Riessen, Arie; Rickard, William; Chon, C.; Kang, N. (Elsevier BV, 2014)
X-ray tomography, mercury intrusion porosimetry, and gas adsorption are used to characterize the nano-scale pore structure of geopolymers with little success. This is because X-ray tomography still lacks high resolution for nanometer-sized pores and the other techniques use the incorrect assumptions of regular pore geometry and interconnected pore systems. To reveal the three-dimensional structure of nanometer-sized pores in coal ash-based geopolymer, conventional bright field electron tomography is used in this study for the first time. Because artifacts resulting from diffraction effects of newly-formed zeolite-like phases are introduced only in the matrix surrounding the pores, the pore size distribution has been investigated successfully. Most of the pores had irregular geometry and were found to range from 20 to 60 nm in equivalent perimeter diameter. The porosity was determined to be 7.15% for the volume of interest, 0.00748 μm3. The first successful outcome of the reported experiment indicates that electron tomography will play an important role in the future for measuring the porosity and pore connectivity of geopolymers enabling predictions of durability and optimization of material properties.